Manipulation of frozen water droplets with nanoparticles - Pae, Mu Xing (2016)
The various benefits of adding nanoparticles to heat transfer fluids brought about the value of studying nanofluids. However, past research has mainly focused on thermal conductivity and stability of nanofluids. With rising interest in using nanofluids as phase change material in thermal energy storage, a study to investigate the freezing mechanism of nanofluids was proposed. Specifically, a parametric study on the drop-wise freezing process of a surfactant stabilized-titanium dioxide nanofluid was conducted. Effect of nanoparticle concentration and size as well as surfactant concentration and type (SDS and CTAB) were investigated. Samples of nanofluids with differing compositions were prepared and deposited drop-wise onto a thermal electric cooler maintained at -200C. The freezing process is recorded with a high speed camera and the results are analyzed thereafter. A difference in the geometry of the frozen nanofluid droplet (a flatten tip) as compared to a frozen pure water droplet (pointy tip) was observed: This novel phenomenon is characterized by a dimensionless diameter ratio between the top and bottom diameter of the flatten droplet. Based on the results, it is concluded the diameter ratio increases at a decreasing rate with an increase in nanoparticle concentration. Different nanoparticle sizes also yield different diameter ratio although no clear relationships can be established. Differing surfactant concentration yield no effects while differing surfactant type yield no significant effects. Proposed further works includes expanding the parametric study to look at effect of environment conditions such as humidity and air temperature, as well as finite element analysis to model the freezing process.